2015
DOI: 10.1121/1.4934559
|View full text |Cite
|
Sign up to set email alerts
|

Talker information influences spectral contrast effects in speech categorization

Abstract: Spectral contrast effects, the perceptual magnification of spectral differences between sounds, have been widely shown to influence speech categorization. However, whether talker information alters spectral contrast effects was recently debated [Laing, Liu, Lotto, and Holt, Front. Psychol. 3, 1-9 (2012)]. Here, contributions of reliable spectral properties, between-talker and within-talker variability to spectral contrast effects in vowel categorization were investigated. Listeners heard sentences in three con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(72 citation statements)
references
References 35 publications
7
65
0
Order By: Relevance
“…This reaffirms arguments that low-level acoustic properties play the primary role in producing SCEs and not higher-level linguistic properties of the precursor sentence (Mitterer, 2006;Laing et al, 2012). This point is also supported by SCEs being produced by a different sentence on every trial (Assgari and Stilp, 2015), unintelligible time-reversed speech (Watkins, 1991), and nonspeech contexts (Holt, 2005(Holt, , 2006Laing et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This reaffirms arguments that low-level acoustic properties play the primary role in producing SCEs and not higher-level linguistic properties of the precursor sentence (Mitterer, 2006;Laing et al, 2012). This point is also supported by SCEs being produced by a different sentence on every trial (Assgari and Stilp, 2015), unintelligible time-reversed speech (Watkins, 1991), and nonspeech contexts (Holt, 2005(Holt, , 2006Laing et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…An exclusionary criterion of failing to achieve at least 80% correct on CV series endpoints was applied (Assgari and Stilp, 2015). This resulted in the removal of one listener's data, so analyses were based on responses from the remaining 18 listeners.…”
Section: Resultsmentioning
confidence: 99%
“…This would involve a comparison between a target sound and its expected realization given a certain context (see, e.g., Assgari & Stilp, 2015;Barreda, 2012;Glidden & Assmann, 2004;Johnson, 1990;Johnson, Strand, & D'Imperio, 1999;Nusbaum & Magnuson, 1997;Nusbaum & Morin, 1992). Support for this interpretation comes from the finding that foreign-accented speech as well as speech that contains fast-speech processes such as segmental reductions and deletions is implicitly perceived as faster (Bosker & Reinisch, 2015;Reinisch, 2016a), possibly due to greater listening effort.…”
Section: Discussionmentioning
confidence: 99%
“…This way of inducing talker variability may not fully represent differences found in actual talkers (Pollack et al, 1954;Watkins, 1991). A more recent study showed that a change in talker can significantly diminish spectral contrast effects and thus challenges this notion that talker information plays no role in spectral contrast effects (Assgari & Stilp, 2015). These experiments EFFECTS OF TALKER ON SPECTRAL CONTRAST EFFECTS 6 added either a +5 dB or a +20 dB spectral peak to sentences from one talker versus 200 different talkers.…”
Section: Effects Of Talker Variability On Spectral Contrast Effectsmentioning
confidence: 93%
“…Even simple compilations of sine tones (or "tone histories") that vary in duration and number of tones can be used to produce the effect (Holt, 2005;Holt, 2006 Stilp et al, 2015). Such large peaks may not be common in natural settings (Assgari & Stilp, 2015). In experiments done by Stilp et al (2015), a significant contrast effect was observed with as small as +5 dB filter gain.…”
Section: Effects Of Talker Variability On Spectral Contrast Effectsmentioning
confidence: 99%